VHF & UHF energy harvesting radio system physical and MAC layer considerations - Zhang, Xiaohu (Kansas State University, 2009)
Wireless Sensor Network industrial and civilian applications have been moved closer to us since they were originally developed for defense applications. They have been or will be widely used in industrial process monitoring and control, earth quake monitoring, healthcare applications, construction health monitoring, home automation, traffic control, and space exploration. The IEEE802.15.4 standard defines the PHY and MAC layers for low power wireless sensor networks. However, applications and research of wireless sensor networking are centered on battery powered devices. To remove the battery from the system is the ultimate goal of this research by using Energy Harvesting technology, which will largely reduce the wireless sensor network maintenance cost, increase the option open to application environments and push the speed of wireless sensor network industrialization. This thesis tackles the problem of RF link budget and PHY layer design for Energy Harvesting Wireless Sensor Network Nodes, through a modification to PHY/MAC layers. To this end, a prototype of energy harvesting radio is developed that hinges on burst-communication and solar cell energy harvesting techniques. The choice of operating frequency is considered relative to transmission range, antenna technology and RF link budget, and quantified by propagation measurements at four unlicensed frequencies in the VHF through UHF spectrums. A short preamble, PHY payload protocol frame structure and synchronization method are also proposed in order to support long sleep period duty cycle necessary in Energy Harvesting Radio systems. Some related work has recently begun under a standardization effort known as 802.15.4f. It is hoped that this thesis will contribute to this effort.
VHF and UHF energy harvesting radio system physical and MAC layer considerations
Keywords: Energy Harvesting; Radio; Wireless Sensor Network; Synchronization; IEEE802.15.4; RF Link Budget; Prototype; Engineering, Electronics and Electrical (0544)